The hydration mechanism of geopolymers based on the activity of solid waste precursors and the evolution of their mechanical properties - Miaomiao Gong; Rui He; Yiyi Wang; Ao Shen; Huaiyi Wang; Linghui Sun; Xiaohan Zhan; Jianshe Liu (PLoS ONE, 2025)
Using slag and fly ash as raw materials to prepare geopolymers is an effective approach to achieving high-value utilization of industrial solid waste and reducing the carbon footprint of building materials. In this study, calcium carbide slag and sodium sulfate were used as composite activators to design three geopolymer systems with high, medium, and low activity. Through multi-scale characterization techniques (XRD/SEM/FTIR/TG-DSC/MIP) combined with mechanical property testing, the performance evolution patterns during the aging hardening process were systematically investigated. The results indicate. The high-activity system exhibits intense early hydration reactions, with compressive strength reaching 46.5 MPa at 28 days (87% of the 90-day strength), indicating that time-dependent hardening primarily occurs in the early stages. The low-activity system exhibits a sustained increase in strength, with a strength growth rate of 51.5% (from 23.9 to 36.2 MPa) between 28 and 90 days. Sodium sulfate significantly enhances late-stage performance by promoting the leaching of [AlO 4 ] 5- . The type of activator and the activity of the precursor significantly influence the mechanical properties and hydration process of geopolymers, providing a theoretical basis for optimizing geopolymer formulations.